1996
DOI: 10.1002/pen.10434
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of biaxially stretched poly(ethylene terephthalate) sheets

Abstract: Huge numbers of PET (polylethylene terephthalate]) bottles are produced in the world. Especially in Japan, the number of hot-fillable PET bottles used is extremely large and is still increasing. This type of bottle is generally manufactured by the heat-set method using hot molds after stretch-blow molding. Herein, we examined how the PET sheet stretching condition affects the PET heat-shrinkage behavior at 85"C, which is the hot-filling temperature. Sheets stretched at a higher temperature and higher speed had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The relaxation time changes not only when the sample is stretched, but also after stretching. Maruhashi and Asada 49 reported that the best thermal stability (in terms of shrinkage) in biaxially stretched PET was found at higher stretching temperature and higher stretching speed. They proposed that the better thermal stability is controlled by the larger number of crystalline regions and the larger relaxed amorphous regions.…”
Section: Resultsmentioning
confidence: 98%
“…The relaxation time changes not only when the sample is stretched, but also after stretching. Maruhashi and Asada 49 reported that the best thermal stability (in terms of shrinkage) in biaxially stretched PET was found at higher stretching temperature and higher stretching speed. They proposed that the better thermal stability is controlled by the larger number of crystalline regions and the larger relaxed amorphous regions.…”
Section: Resultsmentioning
confidence: 98%
“…Early investigations for PET were concerned with its thermal degradation [9][10][11][12][13][14][15] and the kinetics and mechanisms of hydrolytic depolymerization [16][17][18][19]. Previous studies revealed that biaxial stretching of PET films greatly influences the ordered structure and properties of PET [20]. The concerns of PET researchers regarding the effect of biaxial stretching on hydrolytic stability have also been addressed [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization of PET is influenced by various factors, such as molecular weight, orientation, annealing, and crystallization conditions 5. For example, the orientation can cause stress‐induced crystallization and influence the crystallinity 5–9. PET is a semirigid crystalline polymer with slow crystallization behavior; this usually leads to the presence of a large amount of metastable crystals or imperfect crystals that are not at thermodynamic equilibrium.…”
Section: Introductionmentioning
confidence: 99%